2011
DOI: 10.1016/j.actbio.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Covalently immobilized platelet-derived growth factor-BB promotes angiogenesis in biomimetic poly(ethylene glycol) hydrogels

Abstract: The field of tissue engineering is severely limited by a lack of microvascularization in tissue engineered constructs. Biomimetic poly(ethylene glycol) hydrogels containing covalently immobilized platelet-derived growth factor BB (PDGF-BB) were developed to promote angiogenesis. Poly(ethylene glycol) hydrogels resist protein absorption and subsequent nonspecific cell adhesion, thus providing a "blank slate", which can be modified through the incorporation of cell adhesive ligands and growth factors. PDGF-BB is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 37 publications
0
123
0
Order By: Relevance
“…Covalent bonding of growth factors to hydrogel matrix provides a more prolonged release profile, and the conjugated growth factors have more slowly degraded and internalized features. 48,49 Conjugation of bFGF to AC-RYL-PEG-SCM was confirmed via Western blot (Fig. 9A).…”
Section: Effects Of Bfgf Conjugation In Hydrogel Matrices On Msc Diffmentioning
confidence: 87%
See 1 more Smart Citation
“…Covalent bonding of growth factors to hydrogel matrix provides a more prolonged release profile, and the conjugated growth factors have more slowly degraded and internalized features. 48,49 Conjugation of bFGF to AC-RYL-PEG-SCM was confirmed via Western blot (Fig. 9A).…”
Section: Effects Of Bfgf Conjugation In Hydrogel Matrices On Msc Diffmentioning
confidence: 87%
“…48 PEGylated growth factors were proved to maintain their biological activity after chemical coupling and to promote cell-cell contact formation. 49,51,75 The conjugated bFGF not only further promoted the fibroblastic differentiation of HAVIC and ADMSC but also significantly upregulated vimentin expression in BMMSC, which was not achieved by soluble bFGF. This indicated the importance to regulate both internal microenvironment and external environment to drive MSC differentiation toward the target fibroblastic phenotype.…”
mentioning
confidence: 99%
“…51 Several cases have been noted in which PCs were incorporated into hydrogels and biomaterials with coculture of ECs in the areas of vascular grafts, cell sheets, and cell encapsulation. 17,[52][53][54][55][56] Mendes et al 55 showed that perivascularlike cells contributed to the stability of the vascular network of osteogenic tissue formed from cell sheet-based construction. The coculture combination of osteogenic, endothelial, and perivascular-like cells enhanced the vascularization of bone tissue engineering construction.…”
Section: Pcs In Tissue Engineeringmentioning
confidence: 99%
“…The application of perivascular-like cells to cell sheets is potentially promising in the induction of vascularization in three-dimensional construction. Fuoco et al 54 examined the three-dimensional polyethylene glycol-based hydrogel-encapsulated PCs for 56 studied polyethylene glycol-immobilized PDGF-BB hydrogel in order to stimulate PCs and to produce extracellular matrix proteins, fibronectin, collagen, and proteoglycans. Thus, angiogenesis stimulated by PCs in a tissueengineered microsystem formed the basement membrane of capillaries, although polyethylene glycol-immobilized PDGF-BB hydrogel may require clarification for multiple cellular responses, including release of matrix metalloproteinase-2 and -9 and PC stimulation.…”
Section: Pcs In Tissue Engineeringmentioning
confidence: 99%
“…One strategy towards this goal is to develop prevascularized constructs for implantation [7], while other strategies focus on rapid vascular invasion and perfusion [8]. The most promising research has combined these techniques to develop of rapidly vascularized scaffolds that recreate vascular space-filling properties similar to those found in normal, functional tissues, to provide adequate perfusion of implanted constructs [9][10][11].…”
Section: Limitations Of Tissue Engineering: Current Approachesmentioning
confidence: 99%